ANALYSIS OF THE GEOGRAPHICAL CHARACTERISTICS OF LOADING AND UNLOADING AREAS - Sultanov Abdurauf Kamoljon ogli; Rojiyev Xamidullo Xabibullo o‘g‘li; Abdubannopov Abdulatif Abdulhak oglu (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, loading and unloading operations consist of basic and additional operations. Basic operations Selection of the type of vehicle. The type of vehicle is determined by the results of the analysis of the first two items, as well as the relevance of delivery. Out of the four possible, the most suitable were selected based on road, rail, sea and air, geographical conditions, availability of communication routes and cargo characteristics.